PENERAPAN SANKSI PIDANA PASAL 426 KITAB UNDANG-UNDANG HUKUM PIDANA TERHADAP PETUGAS JAGA LEMBAGA PEMASYARAKATAN KELAS II A KABUPATEN BENGKALIS TERHADAP NARAPIDANA YANG MELARIKAN DIRI - Febrianton '; Erdianto Effendi; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Disciplinary action to the watch officer Penitentiary Class II A Bengkalis not provide a deterrent effect. It can be seen a second case of an escaped convict. It is appropriate duty officer who had been negligent in charge of criminal sanctions Criminal Code Article 426 Penal Code, in order to provide a deterrent effect. The purpose of this thesis, Firstly, the adoption of criminal sanctions Article 426 Book of Law Criminal Law against the duty officer Penitentiary Class II A Bengkalis against an escaped convict, Second, obstacles encountered in the implementation of Article 426 Book of Law Criminal Law, third, efforts are being made to prevent the recurrence of escape.This research is a sociological juridical research. This research was conducted at the Penitentiary Class II A Bengkalis, while the sample population is a whole with regard to the issues examined in this study, the data source used, primary data, secondary data, the technique of collecting data in this study with the observation of interviews and literature study.From the research there are three main issues that can be inferred. First, the failure to apply Article 426 Book of Law Criminal Law, Second, barriers do not apply Article 426 Book of Law Criminal Law, namely the shortage of carers and to give fear to other officers to guard prisoners. Third, efforts done Penitentiary Class II A Bengkalis in dealing with inmates who escaped that limit the movement of inmates. Suggestions Author, First, apply Article 426 Book of Law Criminal Law, Second, increasing the number of guard, Third, complementary facilities and infrastructure.Keywords: Criminal Sanctions - Officer of the Watch - Inmates